Baseline characteristics of the 3096 patients recruited into the 'Triple Antiplatelets for Reducing Dependency after Ischemic Stroke' trial. Issue 5 (July 2017) - Bath, Philip MW; Appleton, Jason P; Beridze, Maia; Christensen, Hanne; Dineen, Robert A; Duley, Lelia; England, Timothy J; Heptinstall, Stan; James, Marilyn; Krishnan, Kailash; Markus, Hugh S; Pocock, Stuart; et al.
Background: The risk of recurrence following ischemic stroke or transient ischemic attack is highest immediately after the event. Antiplatelet agents are effective in reducing the risk of recurrence and two agents are superior to one in the early phase after ictus. Design: The triple antiplatelets for reducing dependency after ischemic stroke trial was an international multicenter prospective randomized open-label blinded-endpoint trial that assessed the safety and efficacy of short-term intensive antiplatelet therapy with three agents (combined aspirin, clopidogrel and dipyridamole) as compared with guideline treatment in acute ischemic stroke or transient ischemic attack. The primary outcome was stroke recurrence and its severity, measured using the modified Rankin Scale at 90 days. Secondary outcomes included recurrent vascular events, functional measures (cognition, disability, mood, quality of life), and safety (bleeding, death, serious adverse events). Data are number (%) or mean (standard deviation, SD). Results: Recruitment ran from April 2009 to March 2016; 3096 patients were recruited from 106 sites in four countries (Denmark 1.6%, Georgia 2.7%, New Zealand 0.2%, UK 95.4%). Randomization characteristics included: age 69.0 (10.1) years; male 1945 (62.8%); time onset to randomization 29.4 (11.9) h; stroke severity (National Institutes for Health Stroke Scale) 2.8 (3.6); blood pressure 143.5 (18.2)/79.5 (11.4) mmHg; IS 2143 (69.2%), transient ischemic attack 953 (30.8%). Conclusion: Triple antiplatelets for reducing dependency after ischemic stroke was a large trial of intensive/triple antiplatelet therapy in acute ischemic stroke and transient ischemic attack, and included participants from four predominantly Caucasian countries who were representative of patients in many western stroke services.